Electronic instrument handbook - Coombs, Clyde F. (McGraw-Hill handbooks, 1999)
Design, select and operate the latest electronic instruments. Now in an up-to-the-minute third edition, the bestselling Electronic Instrument Handbook, by top technical author Clyde F. Coombs, Jr. and over 30 leading experts, helps you design, select and operate conventional, virtual, and network-based electronic instruments. From calibration, traceability standards, data acquisition, transducers, analog-to-digital conversion, signal sources, processors and microprocessors, power supplies and more, you move on to current and voltage measurement, signal- and waveform-generation, frequency and time measurement and circuit element measurement instruments, microwave passive devices and digital domain instruments. You learn what every instrument type does.. how it works...and how to get the most out of it.